1982
DOI: 10.1246/bcsj.55.561
|View full text |Cite
|
Sign up to set email alerts
|

Highly Selective Carbon-Carbon Bond Forming Reactions Mediated by Chromium(II) Reagents

Abstract: A low valent chromium reagent is generated from chromium(III) chloride and a half mol of lithium aluminum hydride in tetrahydrofuran. The reagent behaves similarly to anhydrous chromium(II) chloride, which is commercially available, and reduces allylic halides to produce unisolable allylchromium species which add efficiently to aldehydes or ketones with high degree of stereo- and chemoselectivity. Particularly, high threo selectivity is observed in the reaction of aldehydes and 1-bromo-2-butene and is ascribed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
69
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 175 publications
(69 citation statements)
references
References 22 publications
0
69
0
Order By: Relevance
“…25 This aspect also defines the optimum ratio between LiAlH 4 and CrCl 2 as 1:2, which should be carefully adhered to. 8 In the same context, the reader is referred to a convenient synthesis of CrCl 2 (THF) n (n ) 0-2) from cheap CrCl 3 and metallic Cr powder as described by Jolly et al 26 This reduction can be performed on a large scale and ensures that no extraneous metal salts contaminate the reagent. This preparation may help to standardize NHK-type reactions, although it has not yet been widely applied.…”
Section: A Stoichiometric Reactionsmentioning
confidence: 99%
“…25 This aspect also defines the optimum ratio between LiAlH 4 and CrCl 2 as 1:2, which should be carefully adhered to. 8 In the same context, the reader is referred to a convenient synthesis of CrCl 2 (THF) n (n ) 0-2) from cheap CrCl 3 and metallic Cr powder as described by Jolly et al 26 This reduction can be performed on a large scale and ensures that no extraneous metal salts contaminate the reagent. This preparation may help to standardize NHK-type reactions, although it has not yet been widely applied.…”
Section: A Stoichiometric Reactionsmentioning
confidence: 99%
“…In our continued studies of unusual rearrangements of some gem-dihalocyclopropanes, we have reported on the synthesis of the dihalomethyl vinylic compounds of the Hiyama-type reaction for the dihalocyclopropane precursor [1]. The Hiyama reagent Cr +2 is formed in situ by reduction of Cr +3 in DMF with LiAlH 4 , and is typically used to perform the allene synthesis from some specific exocyclic double bonds [2][3][4]. The combined action of the Lewis acid and the red-ox conditions of this reaction were studied for a limited number of substrates, and a rearrangement toward the dihalomethylvinyl was observed in some cases.…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, the formation of allene is expected for some exocyclic double bond originated dihalocyclopropanes [3]. We recently have reported on Eliel's-reagentsinduced reactions of dihalocyclopropane lactones, and demonstrated the formation of allenic derivatives (dihalo, monohalo and fully reduced) from exocyclic methylenes [4,5] with Hiyama reagents in situ formed (Cr +2 /Cr +3 H − , DMF) [6].…”
Section: Introductionmentioning
confidence: 99%